The presence of opera in Lima, its approach and contribution to popular musical activity - Gómez Salinas, Erika Miluska (2023)
The following article has the objective of knowing and valuing the presence of western music in our culture and its influence as a contribution to a new musical development in the Lima area, trying to answer the question: How does western music approach and does it contribute to the popular musical activity in Lima? It can be affirmed that the learning of the European musical structure, especially opera, took great advantage of popular music, thus achieving the consolidation of new sounds, adhered to a need for socio-cultural identity. For this, a musical analysis of the melodic structure of a proclamation composed by Rosa Mercedes Ayarza is made, which embodies in its conception these two aspects, the academic and popular. Since the theme seeks to analyze, interpret and understand cultural and social events, a critical historical-cultural methodology is used to gain knowledge of the musical dynamics of the Lima people of the time.